PENGARUH PENGINTEGRASIAN MATERI KEBENCANAAN KE DALAM KURIKULUMTERHADAP KESIAPSIAGAAN BENCANA GEMPA BUMI DAN TSUNAMI PADA SISWA SEKOLAH DASAR DAN MENENGAH DI BANDA ACEH - Sabri .; Sri Adelila Sari; Sri Milfayetty; M. Dirhamsyah (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2014)
Abstract: Integrating education on disaster risk into the national curriculum and providing save school facilities are two priorities which contributes to the development of a country to achieve the Millennium Development Goal. In developing a safety and preparedness culture especially for children and young generation, Disaster Education is required at the level of primary and secondary schools. The objective of this research was to find out and analyze the influence of integrating material related to disaster in to the curriculum on the student’s preparedness for an earthquake and tsunami at elementary and secondary schools in Banda Aceh. The method used in this research was a quantitative research utilized to collect the data related to the influence of integrating material related to disaster and preparedness for the earthquake and tsunami disasters into the curriculum on knowledge, attitude, participation and competence at schools. The data was collected by using a set of questionnaire and in-depth interview to three school principals from SDN 2, SMPN 1 and SMAN 1. The research results showed that the level of preparedness shown by the students of SDN 2, SMPN 1 and SMAN 1. It was evident from the number of respondents with good levels of preparedness at SND 2 (75.4%) and poor level (24.6%), good levels of preparedness at SMP 1 (75.8%) and poor level (24.2%), good levels of preparedness at SMAN 1 (80.0%) and poor level (20.0%). Based on the statistical analysis, it was found the there was a significant influence of knowledge, attitude, participation and competence on the preparedness shown by students at SND 2 (p-value = 0.0001), SMPN 1 (p-value = 0.0001), and SMAN 1 (p-value = 0.0003) in Banda Aceh, meaning that the difference was found in all schools. It is recommended that the government of Banda Aceh, especially the Department of Education, integrate materials related to earthquake and tsunami disasters into the teaching and learning process. It is also suggested that the students and the teachers keep gaining knowledge on earthquake and tsunami disasters and improving students’ preparedness for a disaster. Keywords: integrating material related to disaster, preparedness, earthquake, tsunami